2021
DOI: 10.53400/mimbar-sd.v8i1.31378
|View full text |Cite
|
Sign up to set email alerts
|

Future Teachers’ Perception towards the Use of YouTube for Teaching-Learning Activities in Nigerian Basic Schools

Abstract: YouTube is one of the most utilized social media in the field of education. Nonetheless, the extent to which the diverse potentials of YouTube are being harnessed in the teaching-learning process is a function of the teachers’ perception. Hence, this study examined future teachers’ perception towards the use of YouTube for teaching-learning activities in Nigerian Basic Schools. The study employed descriptive survey method and 200 future teachers were selected using purposive sampling technique. The respondents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 18 publications
0
4
0
2
Order By: Relevance
“…The results revealed that the ease of use and perceived usefulness significantly affected the intentions of pre-service teachers to use Web 2.0 tools. Furthermore, Ogirima et al (2021) examined teacher candidates' perceptions of the use of YouTube, one of the Web 2.0 tools, in teaching and learning. The study involved 200 pre-service teachers, and a descriptive survey method was used.…”
Section: Problem Statementmentioning
confidence: 99%
“…The results revealed that the ease of use and perceived usefulness significantly affected the intentions of pre-service teachers to use Web 2.0 tools. Furthermore, Ogirima et al (2021) examined teacher candidates' perceptions of the use of YouTube, one of the Web 2.0 tools, in teaching and learning. The study involved 200 pre-service teachers, and a descriptive survey method was used.…”
Section: Problem Statementmentioning
confidence: 99%
“…DeWitt et al (2013) dalam hasil penelitiannya menyebutkan bahwa youtube dapat menjadi media untuk meningkatkan pembelajaran dan pemahaman. Penggunaan multimedia seperti video dapat meningkatkan efektifitas aktivitas pembelajaran [34], [35] karena peserta didik mampu untuk melihat dan mendengarkan kapan saja yang mereka inginkan [20], [33]. Keuntungan lainnya dari adanya youtube sebagai media pembelajaran adalah pengguna internet dapat mengunduh video-video yang ditampilkan di youtube [33].…”
Section: Pembahasanunclassified
“…There are also studies that provide information about digital environments from a holistic perspective (Aytan & Ayhan, 2018). On the other hand, there are also studies examining platforms such as YouTube that allow direct video sharing (Alhamami, 2013;Dizon, 2022;Guihua & Guoxiang, 2022;Ogirima, Tolulope & Temitope, 2021;Srinivasacharlu, 2020;Wang & Chen., 2020). However, it has been observed that there is no research that evaluates the contents of YouTube channels, which are used in the teaching of different languages in integrity.…”
Section: Introductionmentioning
confidence: 99%